Cognitive dysfunction predicts poorer emotion recognition in bariatric surgery candidates. (17th November 2015) - Manderino, L.; Spitznagel, M. B.; Strain, G.; Devlin, M.; Cohen, R.; Crosby, R. D.; Mitchell, J. E.; Gunstad, J.
Summary: Objective: Deficits in traditional cognitive domains (e.g. executive function and memory) are common in persons with severe obesity, but it is unclear if this pattern of dysfunction extends to social cognition. The present study examined whether cognitive impairment was associated with poorer emotion recognition in bariatric surgery candidates. Methods: One hundred sixteen bariatric surgery candidates (mean age = 43.62 ± 11.03; 81% female) completed the computerized Integneuro test battery as part of a larger study visit. In addition to assessing traditional cognitive domains, the Integneuro also includes an emotion recognition measure. This task presents 48 faces (eight different individuals depicting neutral, happiness, fear, sadness, anger and disgust), and participants must choose the correct verbal label from six expression options. Number of correct responses and average reaction time for correct responses served as primary dependent variables. Results: Stepwise multiple regression analyses revealed that older age, more maze errors, and history of hypertension predicted less accuracy in emotion recognition (adjusted R 2 = .22, F [3, 111] = 11.86, p < .001) and that slower switching of attention‐digits, worse long‐delay recall, and older age predicted speed of responses (adjusted R 2 = .26, F [3, 111] = 13.00, p < .001). Discussion: Results show that cognitive dysfunction is associated with poorer performance on a computerized test of emotion recognition, consistent with those in persons with a range of psychiatric and neurological disorders. Additional work is needed to clarify the mechanisms and functional impact of these impairments, especially in relation to weight loss following bariatric surgery.